The Effectiveness of the Modified Think Pair Share Technique with Mind Mapping on EFL Students' Descriptive Writing Ability - Mia Chairunnisa; Cucu Sutarsyah; Budi Kadaryanto (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
This study investigated whether there was a significant difference in descriptive writing ability between seventh-grade EFL students taught using the Modified Think-Pair-Share (TPS) Technique and those taught using the Original TPS Technique. The modification integrated Mind Mapping into the 'Think' phase of TPS, providing students with a structured visual pre-writing scaffold before collaborative discussion and writing. An experimental design was employed involving 61 seventh-grade students at SMPN 22 Bandar Lampung during the 2025–2026 academic year: 31 students in the experimental group (Modified TPS) and 30 students in the control group (Original TPS). Writing ability was measured through pre-test and post-test tasks requiring descriptive texts about animals, scored using Jacobs' (1981) five-aspect analytic rubric—content, organization, vocabulary, language use, and mechanics. The instruments were validated through expert judgment (Aiken's V = 0.9166) and inter-rater reliability was confirmed (pre-test r = .937; post-test r = .925). An Independent Samples t-test on post-test scores yielded t(51.8) = 4.739, p < .001, with the experimental group achieving a significantly higher post-test mean (M = 82.26) than the control group (M = 76.78), and a large effect size (Cohen's d = 1.607). These findings confirm that the Modified TPS Technique is significantly more effective than the Original TPS Technique in improving seventh-grade EFL students' descriptive writing ability.